Effect of Operating Expense on the Profitability of Nepalese Commercial Banks - Ghimire, Anuj; Pradhan, Radhe Shyam (Nepalese Journal of Business, 2024)
This study examines the impact of operating expenses on the profitability of Nepalese commercial banks. Return on assets and return on equity are the selected dependent variables. The selected independent variables are loan loss provision, operational efficiency, capital adequacy ratio, bank size, and inflation. The study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2015/16 to 2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of loan loss provision, operational efficiency, capital adequacy ratio, bank size, and inflation on the profitability of Nepalese commercial banks. The results showed that bank size has a positive impact on return on assets and return on equity. It means that increase in bank size leads to increase in return on assets and return on equity. Similarly, capital adequacy ratio has a positive impact on return on assets and return on equity. It means that increase in capital adequacy ratio leads to increase in return on assets and return on equity. In contrast, loan loss provision has a negative impact on return on assets and return on equity. It means that increase in loan loss provision leads to decrease in return on assets and return on equity. Likewise, operational efficiency has a negative impact on return on assets. It shows that higher the operational efficiency ratio, lower would be the return on assets. Moreover, inflation has a negative impact on return on assets and return on equity. It indicates that increase in inflation leads to decrease in return on assets and return on equity. However, operational efficiency has a positive impact on return on equity. It shows that higher the operational efficiency ratio, higher would be the return on equity.